Exemestane Attenuates Hepatic Fibrosis in Rats by Inhibiting Activation of Hepatic Stellate Cells and Promoting the Secretion of Interleukin 10 - Ya-Hui Wang; Rong-Kun Li; Ying Fu; Jun Li; Xiao-Mei Yang; Yan-Li Zhang; Lei Zhu; Qin Yang; Jian-Ren Gu; Xin Xing; Zhi-Gang Zhang (Journal of Immunology Research)
Exemestane (EXE) is an irreversible steroidal aromatase inhibitor mainly used as an adjuvant endocrine therapy for postmenopausal women suffering from breast cancer. Besides inhibiting aromatase activity, EXE has multiple biological functions, such as antiproliferation, anti-inflammatory, and antioxidant activities which are all involved in hepatic fibrosis. Therefore, we investigated the role of EXE during the progress of hepatic fibrosis. The effect of EXE on liver injury and fibrosis were assessed in two hepatic fibrosis rat models, which were induced by either carbon tetrachloride (CCl4) or bile duct ligation (BDL). The influence of EXE treatment on activation and proliferation of primary rat hepatic stellate cells (HSCs) was observed in vitro. The results showed that EXE attenuated the liver fibrosis by decreasing the collagen deposition and α-SMA expression in vivo and inhibited the activation and proliferation of primary rat HSCs in vitro. Additionally, EXE promoted the secretion of antifibrotic and anti-inflammatory cytokine IL-10 in vivo and in HSC-T6 culture media. In conclusion, our findings reveal a new function of EXE on hepatic fibrosis and prompted its latent application in liver fibrotic-related disease.